ULAMA NUSANTARA ABAD KE-19: MASA PENJAJAHAN DAN PUNCAK INTELEKTUAL HARAMAIN - Firdaus, Syarif; Imawan, Dzulkifli Hadi (Universitas Muhammadiyah Surabaya, 2024)
This article examines the intellectual dynamics of Nusantara scholars in the 19th century, a period marked by the paradox of colonial oppression at home and outstanding achievements in the Islamic scholarly centers of Haramain (Mecca and Medina). Using a historical-descriptive approach, this study explores how Dutch colonial pressures actually propelled the intellectual journeys of Nusantara scholars to the Middle East. The main focus is on the contributions of figures such as Sheikh Nawawi al-Bantani and Sheikh Mahfudz at-Tarmasi, who attained prominent positions in Haramain. This article analyzes their contributions to teaching, writing influential works, and forming transnational intellectual networks. Furthermore, it discusses the impact of these achievements on the development of Islamic thought in Nusantara, including their influence on reform movements and resistance against colonialism. The article concludes by highlighting the resilience and intellectual brilliance of Nusantara scholars who, despite facing adversity at home, managed to reach the pinnacle of scholarly excellence on the global stage. These achievements not only constitute a historical pride but also lay a crucial foundation for the development of Islamic discourse and intellectual identity in Indonesia in subsequent periods.